An Embedded Iris Image Acquisition Research - Dangui Chen; Guojun Qin (Institute of Advanced Engineering and Science, 2017)
In view of the limitation of traditional identification, it is easy to lose and copy keys, cards or ID cards, and it is easy to forget the password. Here, an embedded application system was designed based on the iris identification technology, the functions of gathering, inputing, and registering the iris information and identification can be realized. The system architecture was designed by using the embedded microprocessor of advanced RISC machines (ARM), which is used as the core. The iris sensor was used to gather the iris information, and the development of software was accomplished with the embedded OS Windows CE. The system can be used on the company entrance guard system, customs security of airport and criminal identification.